Wakaf Asuransi Syariah Perspektif Maqashid al-Shariah al-Ghazali - Moh Subhan (ASASI: Journal of Islamic Family Law, 2023)
Waqf is one of the teachings of Islam that has dimensions of worship (ubudiyah) and economic (iqtishodiyah). Waqf functions as a source of funding for the Muslim community, which is utilized to support educational activities, research and study, hospitals, and social services. The concept of Waqf continues to evolve with the development and progress of time. The derivatives of Waqf products have become more diverse, ranging from conservative forms of Waqf to productive Waqf. One of the forms of productive Waqf that emerged in the 2020s is Waqf insurance, where this model of Waqf provides not only protection but also a continuous investment in rewards for the Waqif (the one who donates the Waqf). Waqf in Sharia-compliant insurance products differs from the general concept of Waqf that has been practiced by the community. Sharia-compliant insurance Waqf provides convenience for the community to engage in Waqf by utilizing the benefits of insurance and the benefits of investment in Sharia-compliant insurance. In the context of Maqasid al-Shariah (the objectives of Islamic law) according to Al-Ghazali, the Waqf products of insurance benefits and investment benefits have significant significance in terms of maslahah dharuriyah, which is to protect the five essential elements, namely ijabiyah (affirmation) and salbiyah (negation). In this context, Sharia-compliant insurance Waqf can provide benefits by empowering the community through healthcare financing, education, poverty alleviation, and creating social welfare.